An analysis of tertiary education among dependent and independent workers: The case of Portugal (2006-2016) - Carla Sofia Pires de Carvalho Oliveira Silva; María Jesús Freire Seoane; Beatriz López Bermúdez (Arizona State University, 2019)
The labor insertion of the population is a complex process, which requires the consideration of a good number of variables and the approach from multiple levels. On the one hand, it is important to analyze this procedure according to the conditions of the labor market and the characteristics of the individuals that make up the existing human capital in each country. Portugal has experienced in the period from 2006 to 2016 a process of economic crisis (2008), which provoked in 2011 the intervention of the European Union. In spite of everything, in this context where the socio-economic situation is impaired, the recovery becomes latent and the growth path has been maintained, which has had an impact on educational levels and labor insertion. The main objective of this research is to analyze the levels of tertiary education reached by the employed population in the period 2006 to 2016, differentiating between workers hired by third parties (dependents) or self-employed (independent).